E-Learning Management Systems- A Feature-based Comparative Analysis - Salah, Saeed; Thabet, Mahmoud (Journal of Information Systems and Technology Management, 2021)
One of the main important resources for higher education is a Learning Management System (LMS), which has shown an enhancement of students’ progress with high quality learning outcomes worldwide. Many e-learning tools exist, each one has its own weaknesses and strongest points to the online learning process. This number increases continuously, and the existing tools are being updated, redeveloped, and upgraded. The aim of this study is to present a comprehensive comparative analysis between existing e-learning management systems. Unlike other relevant studies that have narrow scope either in terms of the number of tools or the number of comparative features, this work considers top twenty, highly recommended tools, both open source and commercial. Furthermore, more than twenty evaluation features were used carefully to fulfil students’ and instructors’ current needs. The results of this study have shown that Moodle outperforms the others and it is considered as the best free open source tool for educational purposes. It supports more than 100 different languages and provides its services to more than tens of millions of customers worldwide. Besides to Moodle, Chamilo, TotaraLearn, Open edX and Sakai have more built-in features that provide services to educational institutions. Also, this study showed that Docebo, SkyPrep, ProProfs, SAP Litmos, Moodle, TotaraLearn, Open edX and Opigno systems have more built-in security mechanisms such as antispam, antivirus, IP Blocker, data protection and complex password enforcement. Most considered systems have gamification features except Schoology, ATutor, Sakai, and Ilias, and most commercial systems can offer 24/7 customer care services, except Edmodo and Telnet, whereas open source tools offer this service on specific time slots except Opigno, Ilias, TotaraLearn, Chamilo, and Canvas where the service is offered 24/7.